SOURCE STUDIES AND HISTORIOGRAPHY OF THE SASANIAN PERIOD - Urolov Orzubek (TADQIQOTLAR.UZ, 2024)
Abstract.This article delves into the rich tapestry of sources pertaining to the Sassanid era, a pivotal period in Persian history (224-651 CE). It critically examines a variety of primary sources, including archaeological findings, inscriptions, numismatic evidence, and contemporary literary texts. By analyzing these materials, the article seeks to illuminate the socio-political, cultural, and religious dynamics of the Sassanid Empire. Special attention is given to the interplay between Persian and neighboring cultures, as well as the influence of Zoroastrianism and other belief systems. Furthermore, the article addresses methodological challenges in source interpretation, emphasizing the need for interdisciplinary approaches to fully understand this complex historical landscape.